INCLUSIVE EDUCATION, SUBJECTIVITY, AND THE RIGHT TO PARTICIPATION: A CASE STUDY IN ELEMENTARY EDUCATION - Machado Ferreira, Jaqueline; Medeiros de Aquino, Dyrajaia; Xavier Dantas, Veridiana (Revista Gênero e Interdisciplinaridade, 2025)
This article analyzes the challenges and possibilities of school inclusion based on the case study of Marcio, a 12-year-old student in the 7th grade of elementary school at a municipal public school in Itajaí (SC). Marcio presents behaviors characteristic of the autism spectrum, such as difficulties in self-regulation, a need for predictability, and social isolation. The study discusses how the school can ensure the right to inclusive education regardless of medical reports, based on authors such as Vygotsky, González Rey, and Freire, as well as national legislation: the Law of Guidelines and Bases of National Education (LDB/1996), the Brazilian Law for the Inclusion of Persons with Disabilities (LBI/2015), and the National Curriculum Guidelines (DCNs). The results indicate that inclusion is not limited to enrollment or physical presence, but requires pedagogical, cultural, and attitudinal changes. This article argues that school inclusion demands flexible pedagogical practices, intentional social mediation, and dialogue with the family, reaffirming that diversity is a constitutive element of education.